Prevalence and Risk Factors Associated with Some Intestinal Parasitic Infections among School Children in Yenagoa Metropolis, Bayelsa State, Nigeria - Otumbere Etiefa; Imarenezor Edobor Peter Kenneth; Efere Y. Samson; Elkanah Edet Usodo; Buta Tarimotimi Sam (Kwaghe International Journal of Sciences and Technology, 2026)
Intestinal parasite infections (IPIs) remain a major public health problem among school-aged children in Nigeria, with differing school environments and socio-economic conditions potentially shaping transmission dynamics. This study investigated the prevalence of IPIs and associated risk factors among children attending public and private primary schools in Yenagoa Metropolis, Bayelsa State, and compared prevalence patterns between these settings. A cross-sectional descriptive design was employed, and a total of 395 stool samples were collected from pupils in 10 primary schools (5 public and 5 private). Stool specimens were examined using direct wet mount and formal ether concentration techniques, while socio-demographic and risk-factor data were obtained through structured questionnaires. Associations between infection status and socio-economic variables were assessed using chi-square tests. The overall prevalence of IPIs was 23.8%, with slightly higher prevalence in public schools (25.7%) than in private schools (21.8%). The most frequently identified helminths were Ascaris lumbricoides, Trichuris trichiura, and Strongyloides stercoralis, while Entamoeba histolytica and Giardia lamblia were the predominant protozoa. Infection was most common among children aged 8–10 years (26.6%), and female pupils aged 11–13 years in public schools showed relatively higher infection rates, although no statistically significant differences were detected across age categories or between genders within and across school types. The findings underscore a moderate overall prevalence of intestinal parasites and highlight the continued vulnerability of primary school children to both helminthic and protozoan infections. The study concludes that improving hygiene practices, sanitation infrastructure, and access to clean water in both public and private school communities is essential to reduce transmission and protect child health in Yenagoa Metropolis.